DESIGNING A JAVANESE SCRIPT LEARNING MOBILE APPLICATION USING A PROTOTYPE MODEL - Endang Sri Palupi (Kresnamedia Publisher, 2020)
Javanese script is one of the special characters that need to be studied specifically. At the elementary to high school level in central Java province, there are regional language subjects, namely Javanese language that has Javanese script. Javanese characters are different from the Latin writings used daily, so it requires special understanding and teaching. There are still many students who have difficulty learning Javanese script and limited learning time in elementary school for Javanese language subjects. In addition to helping students to learn Javanese characters more easily, this application is designed so that outsiders can also learn Javanese characters to preserve the culture and love the culture in Indonesia more. The method used in the development of mobile applications is the prototype model with this modelhe author can interact directly with the user so that it can tell the difficulty, provide inputs on what can be set on the application, and what is needed by the user. This application can be useful to learn Javanese characters by utilizing information technology according to the development of the times.